The role of the Chinese piano school in the formation of the Chinese piano art - Yiran, Feng (Linguistics and Culture Review, 2021)
The relevance of the study is that the integrative role of compulsory piano learning in music education acquires the knowledge and skills of conscious work, which is considered the mainstream of the formation of the art of pianism in China. Most of it is conducted and implemented in territorially different environments of music schools to acquire knowledge, themes of perception of musical text, recognizing the degree of use of inherent potential of additional piano features related to increasing the effectiveness of learning activities. In the context of piano schools, a large number of students perceive the subject only as a hobby. For them, these measures are often reduced to the implementation of appropriate programmes. The piano, like any other subject, develops musicality and promotes reflection on the music piece. For some, the musical art of pianism acts as the only way to stimulate the harmonious imagination through which it is possible to learn to listen to chords. The piano is a unique source of inspiration for further musical development. The aim of the study is to reveal and examine the role of the Chinese piano school in the formation of Chinese art of pianism.